ABANDONED TO DIFFERENCE: IDENTITY, OPPOSITION AND TRINH T. MINH-HA'S REASSEMBLAGE - Hill, Michael (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1993)
This essay is about the realization of power's proximity, and about how, once taken seriously, power forces us (1) to disband the outmoded notion of representing a generalized Other, and (2) abandon the Other's co-ordinate, subjective political agency. A tentative premise describes how the proximity of power — its stickiness — forces us to seek more politically informed notions about otherness and identity than could previously be thought. Upon that basis, an argument is built on behalf of a politics that attempts to exceed subjective agency by abandoning identity to politics, rather than abandoning politics to identity. Althusser, Foucault, West, Mudimbe, and Trin Minh-ha are brought into the discussion.